Emerging Trends of Acquisition in Public Libraries of Pakistan: Challenges and Issues - Bashir, Faiza; Hanif Soroya, ,Saira; Soroya, M. Shahid; Khanum, Almas (Library Collections, Acquisitions, & Technical Services, 2015)
Acquiring material in public libraries is a core library activity to fulfill the unique needs of the reader's community. The present study aims to explore the trends of monograph acquisition in public libraries. The population consists of the four major public libraries of Lahore. A case study approach has been used to achieve the objectives of the study. Research is based on primarily the personal visits of the researcher to the acquisition departments of these libraries in order to collect data. Structured interviews were carried out with acquisition librarians to investigate the process of purchasing. The analysis of data reveals that a high ratio of Urdu language books has been purchased during the last decade, literature and religion being the major purchase area, whereas, art and architecture, pure sciences, and languages are the most neglected. The findings further revealed that the studied libraries have primarily been using traditional and informal techniques for acquiring material.
Keywords: Pakistan librarianship; acquisition trends; dept.ils; monograph acquisition; public libraries